Acute onset monoparesis in newly diagnosed patients with type 2 diabetes mellitus with poor glycemia - Raina, Rohit; Fatima, Mukaresh; Wangnoo, Areca (International Journal of Research in Medical Sciences, 2020)
In newly diagnosed patients with diabetes with poor glycemia, presentation is sometimes acute onset monoparesis, which eventually improved with good glycemic control. To report an unusual patient with newly diagnosed diabetes whose initial manifestation was acute onset monoparesis. A 58-year old female patient with new onset type 2 diabetes mellitus with diabetic ketoacidosis (DKA) who presented to us with acute onset monoparesis (right lower limb) lower motor neuron (LMN) type without bladder involvement, secondary to poor glycemia which eventually resolved with good glycemic control.